VARIASI PENAMBAHAN MIKROORGANISME LOKAL (MOL) TAPE SINGKONG TERHADAP C/N RASIO KOMPOS DENGAN METODE AEROB DALAM PEMBUATAN KOMPOS ORGANIK DI PT SANBE FARMA UNIT III - Farida Nur Aisyah; Dindin Wahyudin; Teguh Budi Prijanto (Politeknik Kesehatan Kemenkes Bandung, 2021)
Sanbe Farma Unit III generates waste from its activities. Garbage that continues to accumulate can cause negative impacts on health and the environment. Negative impacts on health can result in diarrhea, vomiting, dengue fever, and also typus.More organic waste management is needed, so it is necessary to make an effort to reduce and manage the timbulan sampah. One of the many attempts is the production of organic waste composting. The research was conducted to understand the difference between variations of local microorganisms (MOL) of cassava tape on the C/N compost ratio by aerob's method of producing organic compost in PT. Sanbe Farma Unit III. MOL variation of cassava tape is use 10ml, 20ml, and 30 ml with 6-time loop for every variation. This type of research is experimental in post test only with control design. The sample used in this research was a park trash taken from PT. Sanbe Farma Unit III. The composting process time is 18 days. The results of the statistic test using one-way Anova test showing p-value 0,021 ≤ 0,05 then Ho is denied, the meaning is there is a C/N difference of meaningful ratio of each treatment. The most effective cassava tape MOL is 30-ml variety based on the physical quality of dark brown and stinks of dirt-compost, with the highest shrinkage of litter at 35.8%, the C/N ratio was 15.57 which met standards according to the 2004 19-7030 SNI on the compost specs of domestic organic garbage. It is recommended to make further observations about the combination of adding organic waste.